2020
DOI: 10.1371/journal.pone.0230867
|View full text |Cite
|
Sign up to set email alerts
|

A novel bi-objective model of cold chain logistics considering location-routing decision and environmental effects

Abstract: Economic, environmental, and social effects are the most dominating issues in cold chain logistics. The goal of this paper is to propose a cost-saving, energy-saving, and emissionreducing bi-objective model for the cold chain-based low-carbon location-routing problem. In the proposed model, the first objective (economic and environmental effects) is to minimize the total logistics costs consisting of costs of depots to open, renting vehicles, fuel consumption, and carbon emission, and the second one (social ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…In Leng et al [2], a novel bi-objective model for the LRPCCL was proposed, which handles the cargo quality decay as the second objective. Leng et al [15] developed several novel solution methods (i.e., decomposition-based hyper-heuristic approaches) to solve the bi-objective model proposed by Leng et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…In Leng et al [2], a novel bi-objective model for the LRPCCL was proposed, which handles the cargo quality decay as the second objective. Leng et al [15] developed several novel solution methods (i.e., decomposition-based hyper-heuristic approaches) to solve the bi-objective model proposed by Leng et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al [11] suggested a two-layer genetic algorithm to resolve an optimization model providing the shortest outbound time of all outbound orders in certain historical periods. Leng et al [12] constructed a biobjective model, which helps achieve cost saving, energy saving, and emission reduction for the cold chain-based lowcarbon location-routing problem that was a simple and efficient framework combining seven well-known multiobjective evolutionary algorithms. Haoxiang et al [13] put forward an adaptive multiobjective genetic algorithm aiming at reaching the highest efficacy and shelf stability for the efficiency of warehousing.…”
Section: Introductionmentioning
confidence: 99%
“…Result showed that the method is quite efficient and produces higher quality solutions. (8) A novel multi-objective hybrid quantum immune algorithm was proposed based on cloud model to improve the delivery efficiency and reduce the cost of distribution requirements. Results showed that C-HQIA is an efficient algorithm for the GVROP.…”
Section: Introductionmentioning
confidence: 99%
“…Results appears that the approach performs exceptionally well to recognize customer groups and connects individual customer's benefits in VRP. (13) Youssef Harrath, A. F. (2019) proposed a two-part chromosome crossover to solve Multiple Travelling Salesman Problem. In their work a genetic algorithm was used to find the best solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation